Government Lawyers and Confidentiality Norms - Kathleen Clark (Washington University Law Review, 2007)
Part I of this Article outlines the lawyer’s confidentiality obligation, which is both strict and broad. One of the exceptions to that obligation, however, is that clients can consent to disclosure. Thus, Part II examines in some depth the identity of the government lawyer’s client, and concludes that no single definition of a client applies to all government lawyers. Instead, one must examine the structure of authority within the particular government context where the lawyer works. Only with such a contextualized and structural analysis can one properly identify the government lawyer’s client and the extent of the lawyer’s authority to make decisions on behalf of that client. In addition, Part II notes that certain government lawyers are authorized to make decisions that are normally in the hands of clients. Part III explains the specific ways in which government lawyers’ confidentiality obligations differ from those of private sector lawyers. First, policy concerns and specific whistleblowing protection laws suggest that government lawyers may disclose government wrongdoing. Second, as a substantive matter, government lawyers must be permitted to disclose information that is subject to mandatory disclosure under open government laws. Since this could result in a chaotic situation with each government lawyer applying her own conception of open government laws, this Article recommends that governments adopt a set of procedures that lawyers can use to get approval of such disclosures. To that end, Part III sets out the substantive standard for the government lawyer’s confidentiality obligation. Part IV recommends the adoption of specific procedures so that government lawyers can make these disclosures in an orderly fashion, providing their clients with advance notice and protecting legitimate government interests.
Keywords: Government attorneys; Confidential communications; Confidential communications – Lawyers